2007
DOI: 10.1211/jpp.59.10.0002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human pharmacokinetics—gut-wall metabolism

Abstract: Intestinal mucosal cells operate with different metabolic and transport activity, and not all of them are involved in drug absorption and metabolism. The fraction of these cells involved is dependent on the absorption characteristics of compounds and is difficult to predict (it is probably small). The cells also appear comparably impermeable. This shows a limited applicability of microsome intrinsic clearance (CL int )-data for prediction of gut-wall metabolism, and the difficulty to predict the gut-wall CL (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…where Q muc,i corresponds to the blood flow to intestinal mucosa of any given intestinal compartment 57. The total Q muc is estimated to 0.250 mL/min73 (Tab.…”
Section: Methodsmentioning
confidence: 99%
“…where Q muc,i corresponds to the blood flow to intestinal mucosa of any given intestinal compartment 57. The total Q muc is estimated to 0.250 mL/min73 (Tab.…”
Section: Methodsmentioning
confidence: 99%
“…The overall CL int,i is influenced by the amount/fraction of mature enterocytes involved (functionally mature cells are found at the villi tips), and the villous counter-current exchange system (which enables transport of molecules from arterioles to venules without accessing the enterocytes) (Fagerholm 2007e). Important intestinal efflux proteins, such as MDR1 (P-glycoprotein), MRP2 and BCRP, are not localized on the blood side of enterocytes (TP-search transport database, 2007), which indicates a potential for limited active intestinal active secretion capacity.…”
Section: Evaluation Of Factors Determining Biliary and Intestinal Clementioning
confidence: 99%
“…Several authors have suggested that mucosal blood flow rather than total intestinal blood flow or portal vein blood flow should be used when estimating intestinal metabolism 67–70 . Indeed, from an anatomical point of view, the one‐cell‐thick epithelial layer that contains the oxidative enzymes is supplied exclusively by the mucosal blood flow.…”
Section: Introductionmentioning
confidence: 99%